Analisis Hak Keuangan Dan Fasilitas Hakim Di Bawah Mahkamah Agung Ditinjau Dengan Teori Realisme - Rahadian, Fakhrabiulza Cesar; Amarini , Indriati (Innovative: Journal Of Social Science Research, 2024)
ABSTRAK Pemerintah sudah semestinya menjamin kesejahteraan para hakim yang bekerja atas nama keadilan. Sebab, dengan beban pekerjaan yang tinggi dan tuntutan putusan pengadilan yang berkualitas serta selaras dengan nilai-nilai keadilan, hanya akan tumbuh dari para hakim yang disejahterakan oleh negara. Pasal 3 PP No 44 Tahun 2024 tentang Perubahan Ketiga Atas Undamg-Undang Peraturan Pemerintah Nomor 94 Tahun 2012 Tentang Hak Keuangan dan Fasilitas Hakim Yang Berada di Bawah Mahkamah Agung, yang menyebutkan bahwa gaji pokok dan penghasilan pensiun hakim yang yang tidak lagi digantungkan atau disamakan dengan ketentuan gaji pokok dan pensiun pokok Pegawai Negeri Sipil (PNS), penyesuaian tunjangan jabatan hakim dengan kenaikan berkisar antara 40%-41%. Tujuan penelitian ini adalah menganalisis bagaimana pengaturan hak keuangan dan fasilitas hakim dan menganalisis bagaimana pelaksanaan hak keuangan dan fasilitas hakim ditinjau dengan teori realisme hukum. Penelitian ini menggunakan metode yuridis normatif. Hasil penelitian bahwa pengaturan tentang hak keuangan dan fasilitas haklim diatur dalam PP Nomor 44 Tahun 2024 tentang perubahan ketiga atas PP nomor 94 Tahun 2012 tentang Hak Keuangan dan Fasilitas Hakim Yang Berada di Bawah Mahkamah Agung. Fasilitas yang Didapat Hakim Sebagai Pejabat Negara meliputi gaji pokok, tunjangan pokok dan tunjangan lainya. Namun, PP Nomor 44 Tahun 2024 tentang Perubahan Ketiga Atas Undamg-Undang Peraturan Pemerintah Nomor 94 Tahun 2012 Tentang Hak Keuangan dan Fasilitas Hakim belum mengatur mengenai fasilitas perumahan, transportasi, jaminan kesehatan, jaminan keamanan, biaya perjalanan dinas, dan kedudukan protokoler. Kemudian skema kenaikan 40% tersebut tidak merata, khususnya bagi hakim tingkat pertama di Pengadilan Kelas II di Kabupaten/Kota. ABSTRACT The government should ensure the welfare of judges who work in the name of justice. This is because the high workload and the demand for quality court decisions that are in line with the values of justice will only grow from judges who are provided with welfare by the state. Article 3 of Government Regulation No. 44 of 2024 on the Third Amendment to Government Regulation No. 94 of 2012 on the Financial Rights and Facilities of Judges Under the Supreme Court, which states that the basic salary and retirement income of judges who are no longer dependent or equated with the provisions of the basic salary and basic pension of Civil Servants (PNS), adjustment of judges' allowances with an increase ranging from 40%-41%. The purpose of this research is to analyse how the regulation of financial rights and facilities of judges and to analyse how the implementation of financial rights and facilities of judges is viewed from the theory of legal realism. This research uses the normative juridical method, research based on document studies, namely using legal material sources in the form of laws and regulations. The approach method used in this research is a statutory approach. The results of the study show that the regulation on the financial rights and facilities of judges is regulated in Government Regulation Number 44 of 2024 concerning the third amendment to Government Regulation Number 94 of 2012 concerning Financial Rights and Facilities of Judges Under the Supreme Court. Facilities received by judges as state officials include basic salary, basic allowances and other allowances. However, Government Regulation No. 44 of 2024 on the Third Amendment to Government Regulation No. 94 of 2012 on the Financial Rights and Facilities of Judges has housing facilities, transportation, health insurance, security guarantees, official travel expenses, and protocol positions. Furthermore, the 40% increase scheme is not equitable, especially for first level judges in Class II Courts in the Regency/City.